Dynamic Function and Composition Changes of Immune Cells During Normal and Pathological Pregnancy at the Maternal-Fetal Interface - Yang, Fenglian; Zheng, Qingliang; Jin, Liping (Frontiers in Immunology, 2019)
A successful pregnancy requires a fine-tuned and highly regulated balance between immune activation and embryonic antigen tolerance. Since the fetus is semi-allogeneic, the maternal immune system should exert tolerant to the fetus while maintaining the defense against infection. The maternal-fetal interface consists of different immune cells, such as decidual natural killer(dNK) cells, macrophages, T cells, dendritic cells, B cells, and NKT cells. The interaction between immune cells, decidual stromal cells, and trophoblasts constitute a vast network of cellular connections. A cellular immunological imbalance may lead to adverse pregnancy outcomes, such as recurrent spontaneous abortion, pre-eclampsia, pre-term birth, intrauterine growth restriction, and infection. Dynamic changes in immune cells at the maternal-fetal interface have not been clearly stated. While many studies have described changes in the proportions of immune cells in the normal maternal-fetus interface during early pregnancy, few studies have assessed the immune cell changes in mid and late pregnancy. Research on pathological pregnancy has provided clues about these dynamic changes, but a deeper understanding of these changes is necessary. This review summarizes information from previous studies, which may lay the foundation for the diagnosis of pathological pregnancy and put forward new ideas for future studies.